2016
DOI: 10.1021/acs.est.5b05010
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic Sulfur Perturbations on Biogenic Oxidation: SO2 Additions Impact Gas-Phase OH Oxidation Products of α- and β-Pinene

Abstract: In order to probe how anthropogenic pollutants can impact the atmospheric oxidation of biogenic emissions, we investigated how sulfur dioxide (SO2) perturbations impact the oxidation of two monoterpenes, α-and β-pinene. We used chemical ionization mass spectrometry to examine changes in both individual molecules and gas-phase bulk properties of oxidation products as a function of SO2 addition. SO2 perturbations impacted the oxidation systems of α-and β-pinene, leading to an ensemble of products with a lesser d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 81 publications
2
38
0
2
Order By: Relevance
“…In our experiment, the decrease in the SOA yield with SO 2 addition might then not be attributed to its reaction with OH. It is also possible that the SO 2 addition could change the chemistry of the photooxidation process and suppress the oxygenation of products (Friedman et al, 2016;Liu et al, 2015). Comparing the MS results at different initial SO 2 concentrations, the proportion of low molecular weight components increases with increasing SO 2 concentration.…”
Section: Effect Of So 2 On Soa Yieldsmentioning
confidence: 99%
“…In our experiment, the decrease in the SOA yield with SO 2 addition might then not be attributed to its reaction with OH. It is also possible that the SO 2 addition could change the chemistry of the photooxidation process and suppress the oxygenation of products (Friedman et al, 2016;Liu et al, 2015). Comparing the MS results at different initial SO 2 concentrations, the proportion of low molecular weight components increases with increasing SO 2 concentration.…”
Section: Effect Of So 2 On Soa Yieldsmentioning
confidence: 99%
“…Similarly, at low NO x (initial NO < 0.3, α-pinene ∼ 20 ppb), Han et al (2016) found that the acidity of seed has no significant effect on SOA yield from α-pinene photooxidation. In addition, SO 2 was found to influence the gas-phase oxidation products from α-pinene and β-pinene photooxidation, which is possibly due to the change in the OH / HO 2 ratio caused by SO 2 oxidation or SO 3 directly reacting with organic molecules (Friedman et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of SO 2 , enhanced gas-phase products from a-pinene and b-pinene photooxidation were observed with a decreased oxidation state of gas-phase semivolatile species (Friedman et al, 2016). Liu et al (2017) demonstrated that SOA yields of cyclohexene photooxidation 55 were lower at atmospherically relevant concentrations of SO 2 , implying that SO 2 may indirectly decrease SOA formation when the acid-catalyzed SOA enhancement is insufficient to compensate for the loss of OH reactivity towards VOCs.…”
Section: Introduction 25mentioning
confidence: 99%